The Relationship between AAS (Addiction Admission Scale) and APS (Addiction Potential Scale) with Timely Graduation of UPH Medical Faculty Students - Pardamean, Engelberta; sungono, veli (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Background: Addiction influential to neurotransmitter damage in the brain, resulting in physical fatigue and behavioral changes that will affect the length of studies of students. The MMPI-2 questionnaire is an instrument used to assess the Addiction Admission Scale / AAS and Addiction Potential Scale / APS.Objective: This study looks at the relationship between AAS and APS with the timely graduation of students.Methods: The study design of this research was cross-sectional for students of the Faculty of Medicine who were running a co-ass program at the Dharmawangsa Mental Hospital and had carried out the MMPI-2 test. Data analysis was done using Stata IC version 16 using t-test, spearman correlation test, and logistic regression.Results: Of the 81 respondents, 67% of women and 33% of men and students who graduated on time amounted to 79%. T-test results obtained an AAS score in the group that was not on time (mean 2.53 ± 1.37) significantly higher than the group that was on time / study period of 5.5 years (mean 1.27 ± 1.56) with a p value of 0.0035. APS has a significant correlation to AAS with a coefficient value of r of 0.2595 and p value of 0.0201. AAS logistic regression test for the accuracy of graduation has a p value of 0.0067 with an OR value of 1.559 (95% CI 1.09-2.21).Conclusion: There is a significant relationship between AAS on time graduation and there is no significant relationship between APS with on timely graduation.